Thermal Impact of Operating Conditions on the Performance of a Combined Cycle Gas Turbine - Thamir K., Ibrahim; M. M., Rahman (Centre of Applied Sciences and Technological Development of the National Autonomous University of Mexico, 2012)
The combined cycle gas-turbine (CCGT) power plant is a highly developed technology which generates electrical power at high efficiencies. The first law of thermodynamics is used for energy analysis of the performance of the CCGT plant. The effects of varying the operating conditions (ambient temperature, compression ratio, turbine inlet temperature, isentropic compressor and turbine efficiencies, and mass flow rate of steam) on the performance of the CCGT (overall efficiency and total output power) were investigated. The programming of the performance model for CCGT was developed utilizing MATLAB software. The simulation results for CCGT show that the overall efficiency increases with increases in the compression ratio and turbine inlet temperature and with decreases in ambient temperature. The total power output increases with increases in the compression ratio, ambient temperature, and turbine inlet temperature. The peak overall efficiency was reached with a higher compression ratio and low ambient temperature. The overall efficiencies for CCGT were very high compared to the thermal efficiency of GT plants. The overall thermal efficiency of the CCGT quoted was around 57%; hence, the compression ratios, ambient temperature, turbine inlet temperature, isentropic compressor and turbine efficiencies, and mass flow rate of steam have a strong influence on the overall performance of the CCGT cycle.